2016
DOI: 10.1007/s00380-016-0909-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in matrix remodeling and early osteogenic markers in aortic valvular interstitial cells

Abstract: Calcific aortic valve disease (CAVD) is a major cardiovascular disorder in the developed countries. Male is a known risk factor in this disease; unfortunately, how sex contributes to CAVD is mostly unknown. The objective of this study is to determine whether valvular interstitial cells (VICs) isolated from male versus female aortic valves demonstrate difference in osteogenic differentiation and/or extracellular matrix (ECM) remodeling. VICs were isolated from male and female rat or porcine aortic valves and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…High levels of ERK phosphorylation were detected in calcified and stenotic human valves [ 72 ]. In support of the hypothesis of early occurrence of sex-specific differences in CAVD pathogenesis, another study using VICs obtained from male and female rat and porcine aortic valves showed that there is a sex-related difference in the events associated with osteogenic differentiation of the aortic VICs, where male VICs are more prone to calcification than female ones [ 73 ]. Human VICs undergo osteoblastic differentiation in response to specific mediators such as BMPs and TGF-β [ 74 ].…”
Section: The Experimental Evidence Indicating Sex-related Differenmentioning
confidence: 96%
“…High levels of ERK phosphorylation were detected in calcified and stenotic human valves [ 72 ]. In support of the hypothesis of early occurrence of sex-specific differences in CAVD pathogenesis, another study using VICs obtained from male and female rat and porcine aortic valves showed that there is a sex-related difference in the events associated with osteogenic differentiation of the aortic VICs, where male VICs are more prone to calcification than female ones [ 73 ]. Human VICs undergo osteoblastic differentiation in response to specific mediators such as BMPs and TGF-β [ 74 ].…”
Section: The Experimental Evidence Indicating Sex-related Differenmentioning
confidence: 96%
“…Supporting the hypothesis that sex-specific divergence of CAVD etiology may occur early on is a growing body of evidence indicating intrinsic cellular-scale differences between men and women [6] that also yield differences in the cellular response to pathological stimuli. For example, VIC culture in hormone-free osteogenic medium is associated with an increase in calcification in male VICs compared to female VICs [9]. The discovery that men and women exhibit different CAVD pathogenesis has the potential to provoke transformative changes in the approach used to investigate CAVD etiology as well as the clinical treatment of this disease.…”
Section: Implications For the Study And Treatment Of Cavdmentioning
confidence: 99%
“…These results have led to a growing interest to better understand the regulatory role of TNF‐α in AVS. Recent studies suggest that TNF‐α induces VIC calcification through both apoptotic and osteogenic mechanisms 38‐41 . For example, VIC mineralization in human valves depends on apoptotic signaling through death receptor 4 caused by increasing expression of the TNF ligand superfamily member 10 (TNF10 or TRAIL) 42 .…”
Section: Introductionmentioning
confidence: 99%